PENGEMBANGAN BAHAN AJAR BERBASIS RISET BAGI DOSEN PERGURUAN TINGGI: “FROM RESEARCH TO CLASSROOM” - Abdillah, Muhammad Rasyid; Anita, Rizqa; Wijanarko, Iwan; Tristiyani, Tristiyani; Rizqi, Liza (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
This community service initiative aimed to strengthen academic leaders’ capacity in developing research-based teaching materials that support evidence-informed learning in higher education. Conducted at XYZ University, Sumatera, the program involved deans, vice deans, and heads of study programs who often face challenges in translating institutional research outputs into effective instructional resources. Through the “From Research to Classroom” framework introduced in a structured workshop, participants were guided to identify pedagogically relevant research insights, extract key findings, and transform them into teaching components aligned with course learning outcomes. The workshop integrated lectures, hands-on exercises, and collaborative peer review to ensure practical skill development. Evaluation results indicated notable improvements in participants’ understanding and ability to convert research findings into modules, case materials, and structured learning activities. Overall, the program demonstrates the importance of capacity-building initiatives for academic leaders in fostering evidence-based teaching practices and narrowing the gap between research production and classroom implementation within Indonesian higher education institutions